Student Character Based on Pancasila Student Profiles at Tarakan City Public Middle School - Suprianto Suprianto; Sitti Hardiyanti Arhas; M. Said Zainuddin; Nurisa Ardiana (Jurnal Ilmiah Ilmu Administrasi Publik, 2022)
Strengthening Character Education is not a new policy at all because since 2010 character education in schools has become a National Movement. Education units are a strategic tool for building national character because they have systems, infrastructure, and educational ecosystem support spread throughout Indonesia, from urban to rural areas. This study aims to describe the character of students based on Pancasila Student Profiles at Public Middle Schools in East Tarakan District, Tarakan City. The research method used was a survey of the research population, namely all-state junior high schools in East Tarakan District with a total sample of 180 students. The distribution of questionnaires is a data collection technique, while the data analysis technique used is descriptive statistics. The results of the research on the description of student character based on the profile of Pancasila students as a whole are in the very good category. Meanwhile, in terms of the Pancasila profile character element indicators in terms of faith, and piety to God Almighty, it is known that the value of 73.33% is in the very good category; In terms of global diversity, it is in the very good category, with an average value of 56.67%; Judging from the dimensions of mutual cooperation, it is in the very good category, with an average value of 46.11%; Judging from the independent dimension, it is in the very good category, with an average value of 48.89%; Judging from the critical dimension, it is in a very good category, with an average value of 45.00%; Meanwhile, in terms of the creative dimension, it is in the good category with an average value of 35.56%.